Magnolia Officinalis Alcohol Extract Alleviates the Intestinal Injury Induced by Polygala Tenuifolia Through Regulating the PI3K/AKT/NF-κB Signaling Pathway and Intestinal Flora - Liu S; Yang D; Li W; Chen Q; Lu D; Xiong L; Wu J; Ao H; Huang L (Drug Design, Development and Therapy, 2024)
Si Liu, Dan Yang, Wen Li, Qiuping Chen, Danni Lu, Liang Xiong, Junjie Wu, Hui Ao, Lihua Huang State Key Laboratory of Southwestern Chinese Medicine Resources, School of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu, 611137, People’s Republic of ChinaCorrespondence: Lihua Huang; Hui Ao, College of Pharmacy, Chengdu University of Traditional Chinese Medicine, Chengdu, 611137, People’s Republic of China, Email huanglihua@cdutcm.edu.cn; aohui2005@126.comPurpose: Polygala tenuifolia Willd. (PT), a traditional Chinese medicinal plant extensively employed in managing Alzheimer’s disease, exhibits notable gastrointestinal side effects as highlighted by prior investigations. In contrast, Magnolia officinalis Rehd. et Wils (MO), a traditional remedy for gastrointestinal ailments, shows promising potential for ameliorating this adverse effect of PT. The objective of this study is to examine the underlying mechanism of MO in alleviating the side effects of PT.Methods: Hematoxylin-eosin (H&E) staining was used to observe the structural damage of zebrafish intestine, and enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of inflammatory factors and oxidative stress. The integrity of the intestinal tight junctions was examined using transmission electron microscope (TEM). Moreover, the expression of intestinal barrier genes and PI3K/AKT/NF-κB signaling pathway-related genes was determined through quantitative real-time PCR. The changes in intestinal microbial composition were analyzed using 16S rRNA and metagenomic techniques.Results: MO effectively ameliorated intestinal pathological damage and barrier gene expression, and significantly alleviated intestinal injury by reducing the expression of inflammatory cytokines IL-1β, IL-6, TNF-α, and inhibiting the activation of PI3K/AKT/NF-κB pathway. Furthermore, MO could significantly increase the relative abundance of beneficial microorganisms (Lactobacillus, Blautia and Saccharomyces cerevisiae), and reduce the relative abundance of pathogenic bacteria (Plesiomonas and Aeromonas).Conclusion: MO alleviated PT-induced intestinal injury, and its mechanism may be related to the inhibition of PI3K/AKT/NF-κB pathway activation and regulation of intestinal flora.Keywords: polygala tenuifolia, PI3K/AKT/NF-κB, gut microbiota, inflammation, intestinal injury